Changes in socio-economic patterns of energy consumption and insufficient energy intake across India from 1993–94 to 2011–12. Issue 2 (15th July 2019) - Perkins, Jessica M; Chakrabarti, Suman; Joe, William; Lee, Hwa-Young; Heo, Jongho; Lee, Jong-Koo; Oh, Juhwan; Subramanian, SV
Abstract: Objective: To assess whether disparities in energy consumption and insufficient energy intake in India have changed over time across socio-economic status (SES). Design: This cross-sectional, population-based survey study examines the relationship between several SES indicators (i.e. wealth, education, caste, occupation) and energy consumption in India at two time points almost 20 years apart. Household food intake in the last 30 d was assessed in 1993–94 and in 2011–12. Average dietary energy intake per person in the household (e.g. kilocalories) and whether the household consumed less than 80 % of the recommended energy intake (i.e. insufficient energy intake) were calculated. Linear and relative risk regression models were used to estimate the relationship between SES and average energy consumed per day per person and the relative risk of consuming an insufficient amount of energy. Setting: Rural and urban areas across India. Participants: A nationally representative sample of households. Results: Among rural households, there was a positive association between SES and energy intake across all four SES indicators during both survey years. Similar results were seen for energy insufficiency vis-à-vis recommended energy intake levels. Among urban households, wealth was associated with energy intake and insufficiency at both time points, but there was no educational patterning of energy insufficiency in 2011–12. Conclusions: Results suggest little overall change in the SES patterning of energy consumption and percentage of households with insufficient energy intake from 1993–94 to 2011–12 in India. Policies in India need to improve energy intake among low-SES households, particularly in rural areas.